4-{[2-(2,4-Dinitrophenyl)hydrazinylidene](phenyl)methyl}-5-methyl-2-phenyl-1H-pyrazol-3(2H)-one ethanol monosolvate - Idemudia, Omoruyi G. (International Union of Crystallography, 2012)
In the title compound, C(23)H(18)N(6)O(5)·C(2)H(6)O, all three benzene rings lie in an approximate plane [maximum deviation = 0.2688 (16) Å] that makes an angle of 53.56 (3)° with the plane of the pyrazolone ring. Intramolecular N—H⋯O hydrogen bonds occur. In the crystal, the ethanol solvent molecule links adjacent molecules through N—H⋯O—H⋯O hydrogen bonds, leading to an infinite chain along the c-axis direction. The ethyl group of the ethanol solvent molecule is disordered over two set of sites in a 0.762 (5):0.238 (5) ratio.